LARGE-SCALE ONLINE LEARNING SUPPORTED BY INTELLIGENT DEVICES IN THE POST-PANDEMIC ERA - Xu, Bingbing; Margeviča-Grinberga, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
With the support of emerging technologies such as artificial intelligence and cloud computing, China began learning and teaching online in 2020 to control the spread of the pandemic and implement the "Classes are suspended, but learning continues" policy. Online learning and teaching require modified methods, management, and evaluation compared with traditional instruction. Moreover, teachers' and students' thinking styles and ways of communication have also changed in terms of practice, places of study and tasks. The large-scale online teaching-learning model has ushered in new teaching and learning reform trends in the post-pandemic era. Therefore, this study investigates students' and teachers' readiness for, acceptance of, and satisfaction about comprehensive online teaching and learning and explores the effect online learning has on students. To achieve the research aim, 67 students from one city and one village in China were surveyed.The results revealed that online teaching was met with medium levels of readiness and acceptance and gave little satisfaction. For students, attitudes toward learning, support (or lack thereof) from instructors, effective interactions, motivation to learn, and self-regulation influenced online learning satisfaction. In addition, the students' grade levels and locations.